Sanitation challenges in Dar Es Salaam: the potential of simplified sewerage systems - Yap, Christopher (Environment and Urbanization)
In the context of growing urbanization, sanitation in many cities is in acute crisis with severe social and environmental consequences. The Sustainable Development Goal (SDG) of sanitation for all by 2030 is increasingly elusive. Municipalities have been experimenting with a range of lower-cost sanitation solutions. Simplified Sewerage Systems (SSS) have emerged in different cities as one response, but with mixed results. This paper evaluates an SSS project in an informal settlement in Dar es Salaam, Tanzania. Drawing on a combination of a survey and focus group discussions, the paper examines the social and economic impacts of the SSS and identifies a set of key concerns for future urban sanitation interventions: affordability, maintenance and governance. We conclude by considering the implications for future research and practice on urban sanitation, including the limits of technology-based approaches and the necessity to focus on the diverse needs of residents in place.- Reproduced
Keywords: Dar Es Salaam, Informal settlement, Simplified sewerage system, Urban inequality, Urban infrastructure, Urban poverty, Urban sanitation